Series expansions in closed and open quantum many-body systems with multiple quasiparticle types - Lenke, Lea; Schellenberger, Andreas; Schmidt, Kai Phillip (Physical Review A, 2023)
The established approach of perturbative continuous unitary transformations (pCUTs) constructs effective quantum many-body Hamiltonians as perturbative series that conserve the number of one quasiparticle type. We extend the pCUT method to similarity transformations - dubbed pcst++ - allowing for multiple quasiparticle types with complex-valued energies. This enlarges the field of application to closed and open quantum many-body systems with unperturbed operators corresponding to arbitrary superimposed ladder spectra. To this end, a generalized counting operator is combined with the quasiparticle generator for open quantum systems recently introduced by Schmiedinghoff and Uhrig [G. Schmiedinghoff and G. S. Uhrig, SciPost Phys. 13, 122 (2022)2542-465310.21468/SciPostPhys.13.6.122]. The pcst++ then yields model-independent block-diagonal effective Hamiltonians and Lindbladians, allowing a linked-cluster expansion in the thermodynamic limit similar to the conventional pCUT method. We illustrate the application of the pcst++ method by discussing representative closed, open, and non-Hermitian quantum systems.
CRIS-Team Scopus Importer:2023-08-18